1983
DOI: 10.1159/000249743
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Chronic Urticaria and Vitiligo, Associated with Thyroiditis, Treated with PUVA

Abstract: A case of chronic urticaria and vitiligo, associated with thyroiditis is described. Significantly elevated thyromicrosomal antibodies were found. Autoimmune reaction is a possible cause of the patient’s thyroid disease, vitiligo and chronic urticaria. Following PUVA treatment with a total dose of 300 J/cm2 the patient’s urticaria subsided in all irradiated areas, only to relapse 2 weeks later. Subsequently courses of PUVA gave periods of remission. The treatment also induced repigmentation in the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 8 publications
0
11
1
Order By: Relevance
“…Midelfart et al . , in a case report found that PUVA treatment with a total dose of 300 J/cm 2 resulted in resolution of the patient's urticaria in all irradiated areas. Conversely, PUVA therapy was ranked as neutral or ineffective using a questionnaire evaluated by Canadian dermatologists and allergists .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Midelfart et al . , in a case report found that PUVA treatment with a total dose of 300 J/cm 2 resulted in resolution of the patient's urticaria in all irradiated areas. Conversely, PUVA therapy was ranked as neutral or ineffective using a questionnaire evaluated by Canadian dermatologists and allergists .…”
Section: Discussionmentioning
confidence: 96%
“…The use of psoralen and ultraviolet A (PUVA) and narrowband UVB (NB‐UVB) in treatment of chronic urticaria was assessed in only few studies. Considering the paucity of studies on the use of phototherapy and photochemotherapy in chronic urticaria, with absence of previous reports on the comparative efficacy of PUVA and NB‐UVB in the disease, we aimed in this work to compare the clinical efficacy of PUVA photochemotherapy and NB‐UVB phototherapy in the treatment of chronic urticaria.…”
mentioning
confidence: 99%
“…Midelfart et al . first reported improvement in CU following PUVA therapy in a patient who had co‐existing vitiligo and CU.…”
Section: Discussionmentioning
confidence: 99%
“…21 Phototherapy is not recommended as a treatment option for such patients in any of the standard urticaria treatment guidelines. Midelfart et al 22 first reported improvement in CU following PUVA therapy in a patient who had co-existing vitiligo and CU. A few subsequent studies reported a beneficial effect of different phototherapeutic modalities in the treatment of CU.…”
Section: Discussionmentioning
confidence: 99%
“…There are little data to support the use of psoralen UVA (PUVA) photochemotherapy and UVB phototherapy for chronic urticaria (159)(160)(161)(162)(163). The efficacy of PUVA therapy in the management of chronic urticaria was assessed by a Canadian group of authors, and it was ranked as neutral or ineffective (164).…”
Section: Puva Chemotherapy and Uvb Therapymentioning
confidence: 99%